Research on patients' views in the evaluation and improvement of quality of care. Issue 2 (1st June 2002) - Wensing, M; Elwyn, G
Abstract : The identification of methods for assessing the views of patients on health care has only developed over the last decade or so. The use of patients' views to improve healthcare delivery requires valid and reliable measurement methods. Four approaches are recognised: inclusion of patients' views in the information to those seeking health care, identification of patient preferences in episodes of care, patient feedback on delivery of health care, and patients' views in decision making on healthcare systems. Outcome measures for the evaluation of the use of patients' views should reflect the aims in terms of processes or outcomes of care, including possible negative consequences. Rigorous methodologies for the evaluation of methods have yet to be implemented.